Effect of ambient temperature on female endurance performance - Renberg, J.; Sandsund, M.; Nordrum Wiggen, Ø.; Reinertsen, R. E. (Journal of Thermal Biology, 2014)
Ambient temperature can affect physical performance, and an ambient temperature range of 4°Cto11°C is optimal for endurance performance in male athletes. The few similar studies of female athletesappear to have found differences in response to cold between the genders. This study investigatedwhether ambient temperature affects female endurance performance. Nine athletes performed six testswhile running on a treadmill in a climatic chamber at different ambient temperatures: 20, 10, 1, 4, 9and 14°C and a wind speed of 5 m s 1. The exercise protocol consisted of a 10-min warm-up, followedby four 5-min intervals at increasing intensities at 76%, 81%, 85%, and 89% of maximal oxygenconsumption. This was followed by an incremental test to exhaustion. Although peak heart rate, bodymass loss, and blood lactate concentration after the incremental test to exhaustion increased as theambient temperature rose, no changes in time to exhaustion, running economy, running speed at lactatethreshold or maximal oxygen consumption were found between the different ambient temperatureconditions. Endurance performance during one hour of incremental exercise was not affected by ambienttemperature in female endurance athletes.